Dampak Stres Kerja, Beban Kerja, Lingkungan Kerja Non Fisik Terhadap Turnover Intention Karyawan ( Studi Kasus Pada Kantor Pengelola Perkebunan PT. Kencana Sawit Indonesia) - Vicky Drigo Wahyu; Zusmawati Zusmawati (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to examine the effect of work stres variables, non-physical work environment on turnover intention of employees at the Plantation Processing Office of PT. Kencana Palm Oil Indonesia. This type of research uses quantitative methods. Data collection is done through questionnaires to 144 respondents using Saturated sampling technique, namely the technique of determining the sample when all members of the population are used as sample.Using instrument testing (validity test and reliability test), classical assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of the study show that work stres has a positive and significant effect on turnover intention, and the non-physical work environment has a positive and significant effect on turnover intention. Where multiple linear regression produces Y = 12,867 + 0.149 (X1) + 0.221 (X2) + 0.091 (X3) and the first hypothesis test shows that the t-count value is greater than t-table (2.386 > 1.655) with a significantly smaller value than the t-table value. alpha (0.018 <0.05). This shows that H1 is accepted, which means that work stress has a positive effect on employee performance. And the second hypothesis test shows that the t-count value is greater than t-table (3.654 > 1.655) with a significantly smaller value than the alpha value (0.000 <0.05). This shows that H2 is accepted, which means that workload has a positive effect on employee performance. And the third hypothesis test shows that the t-count value is greater than t-table (2.082 > 1.655) with a significantly smaller value than the alpha value (0.039 <0.05). This shows that H3 is accepted, which means that the non-physical work environment has a positive effect on employee performance.